1 zany zoo = 1 zoo loco - Degman, Lori.; Jack, Colin (New York : Simon & Schuster Books for Young Readers, 2010)
When one fearless fox grabs the zookeeper's keys and opens all the cages, increasing numbers of animals behave in most unusual ways.
Ages 3 and up.
In English and Spanish.
Keywords: Zoo animals -- Juvenile fiction; Counting -- Juvenile fiction; Spanish language materials; Stories in rhyme; Fiction